Identification of Pathogenic Bacteria in Traditional Packaged Donuts at Ampenan Market Using Xylose Lysine Deoxychoalate (XLD) Media - Suripto; Chalida Alfani (Universitas Mataram, 2022)
Snacks in traditional packaging are a type of food favored by the community. However, not a few buyers and sellers are not aware of the importance of cleanliness of these favorite foods from contamination with pathogenic bacteria that can cause illness for people who eat them. Many of them also do not know and are skilled at checking whether the food is clean from germs or not. This study aims to transfer knowledge and skills to identify bacteria in donuts in Ampenan Market using xylose lysine deoxychoalate (XLD) media. Samples of donut snacks in traditional packaging were taken from the Ampenan market in Mataram City and then examined for the content of pathogenic bacteria in the laboratory at The Mataram Laboratory Hall for Health, Testing and Calibration. The examination began with the isolation of bacteria from the sample on Selenit Broth Media in 24 hours incubation at 350C then continued with the isolation of Salmonella on selective agar media, namely XLD. The results of the isolation were examined and identified by Gram staining and bio-chemical assayt of control sugar and Salmonella suspect, oxidase and catalase tests. The results showed that Selenit Broth media could multiply and repair Salmonella cells and XLD media could separate it from other bacteria in the Gram stain. Gram stain, biochemical test, oxidase test and catalase test showed the presence of Gram negatif bacteria which was confirmed as Salmonella in the sample.